Synthetic lethal gene pairs: Experimental approaches and predictive models - Tang, Shan; Gökbağ, Birkan; Fan, Kunjie; Shao, Shuai; Huo, Yang; Wu, Xue; Cheng, Lijun; Li, Lang (Frontiers in Genetics, 2022)
Synthetic lethality (SL) refers to a genetic interaction in which the simultaneous perturbation of two genes leads to cell or organism death, whereas viability is maintained when only one of the pair is altered. The experimental exploration of these pairs and predictive modeling in computational biology contribute to our understanding of cancer biology and the development of cancer therapies. We extensively reviewed experimental technologies, public data sources, and predictive models in the study of synthetic lethal gene pairs and herein detail biological assumptions, experimental data, statistical models, and computational schemes of various predictive models, speculate regarding their influence on individual sample- and population-based synthetic lethal interactions, discuss the pros and cons of existing SL data and models, and highlight potential research directions in SL discovery.